Conversion of canola oil and canola oil methyl ester (CME) to green aromatics over a HZSM-5 catalyst: a comparative study. Issue 36 (23rd April 2015) - Bayat, A.; Sadrameli, S. M.
<x xml:space="preserve">Abstract</x> The catalytic conversions of canola oil and canola oil methyl ester (CME) for the production of green aromatics over a HZSM-5 catalyst were investigated.